ANALYSIS OF THE LEVEL OF ROAD DAMAGE USING THE PAVEMENT CONDITION INDEX (PCI) METHOD: A CASE OF JALAN LASWI MAJALENGKA - Arif Pajar Maullana; Indrastuti (Fakultas Teknik Sipil dan Perencanaan, 2024)
In Majalengka Regency, the Laswi road is an access road that connects the Tonjong Roundabout with the Tonjong Kecap Monument. The pavement on Jalan Laswi uses flexible pavement. The road was damaged due to the large number of heavy and light vehicles that passed through it. It is anticipated that the assessment of road damage conditions will be able to assess the degree of road damage on a section of the road. The purpose of this study is to determine the appropriate method of handling road damage and the level of damage that occurs. The PCI method (Pavement Condition Index) is used to assess the condition of road pavement damage. This method involves a visual survey of the damage and evaluating it according to type, extent, and amount. The damage can be used as a basis for performing maintenance and repair tasks. By using the PCI method, research on road conditions in Laswi (Majalengka Regency) found that the average PCI value for all Laswi road sections was 82,38% (Very Good).